2020
DOI: 10.2196/19300
|View full text |Cite
|
Sign up to set email alerts
|

Email Use Reconsidered in Health Professions Education: Viewpoint

Abstract: Email has become a popular means of communication in the past 40 years, with more than 200 billion emails sent each day worldwide. When used appropriately, email can be an effective and useful form of correspondence, although improper practices, such as email incivility, can present challenges. Email is ubiquitous in education and health care, where it is used for student-to-teacher, provider-to-provider, and patient-to-provider communications, but not all students, faculty members, and health professionals ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Emails messages with politeness motivate academics to work with students by making students appear more competent and successful (Bolkan & Holmgren, 2012). There are many studies showing the necessity of training on email etiquette of students (De Gagne et al, 2020;Özçakmak & Hakkoymaz, 2017;Kim, et al, 2016;Lewin-Jones & Mason, 2014;Pignata et al, 2015). The results of this study revealed that more than half of the students wanted to get training in communication ethics in academic emails.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Emails messages with politeness motivate academics to work with students by making students appear more competent and successful (Bolkan & Holmgren, 2012). There are many studies showing the necessity of training on email etiquette of students (De Gagne et al, 2020;Özçakmak & Hakkoymaz, 2017;Kim, et al, 2016;Lewin-Jones & Mason, 2014;Pignata et al, 2015). The results of this study revealed that more than half of the students wanted to get training in communication ethics in academic emails.…”
Section: Discussionmentioning
confidence: 87%
“…However, it is necessary to pay attention to netiquette, cyber incivility, formality. Email communication in an academic setting can present challenges related to workload and compromised relationships (De Gagne et al, 2020). To be taken seriously and considered reliable, the following should be avoided in email correspondence: use of emojis, informal language, misspellings, and grammatical errors, and disregard for upper-/lower-case (Dumbravă &…”
mentioning
confidence: 99%
“…The one exception was email, which was the only method not associated with higher family communication quality. While emails may be utilized effectively in clinical settings between patients and providers or in work settings [ 32 , 33 ], its rigid and professional nature may hinder communication quality within families. Email incivility, or rudeness through email communication, is also common and can have negative impacts [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…While emails may be utilized effectively in clinical settings between patients and providers or in work settings [ 32 , 33 ], its rigid and professional nature may hinder communication quality within families. Email incivility, or rudeness through email communication, is also common and can have negative impacts [ 33 ]. Our null result suggests that our positive results on other sharing methods were unlikely due to social desirability bias and indicates that email is not a preferred method of family communication.…”
Section: Discussionmentioning
confidence: 99%
“…Learning and practicing basic dining etiquette cannot be overestimated for professional presence (Bass, 2019). Professional development also includes learning responsible email writing (De Gagne et al, 2020). Students learn basic email etiquette, email composition with subject lines, effective email closings, and ethical and legal implications.…”
Section: Provide Professional Development Opportunitiesmentioning
confidence: 99%